Fabrication and characterization of poly(vinyl alcohol)- graphene quantum dot-cobalt oxide/poly(3,4- ethylenedioxythiophene) for high-performance supercapacitor - Syed Zainol Abidin, Shariffah Nur Jannah (2017)
Fabrication of highly conductive nanofiber by coating polyvinyl alcohol-graphene quantum dot-cobalt oxide (PVA-GQD-Co3O4) nanofiber composites with a conductive material, poly(3,4-ethylenedioxythiophene) (PEDOT) for symmetrical supercapacitor was prepared via two-step technique i.e. electrospinning and electropolymerization. The prepared electrode materials were characterized using Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy and X-ray diffraction (XRD) analysis to confirm the structure of the electrospun nanofiber composites. The presence of cauliflower-like structure studied by field emission scanning electron microscopy (FESEM) revealed that PEDOT was uniformly coated on PVA-GQD-Co3O4 electrospun nanofibers. The limited cycling stability of PEDOT, poor capacitance of GQDs and low conductivity of Co3O4, were overcome by forming the nanofiber composite. The electrochemical performance were investigated and evaluated by sandwiching a filter paper immersed in a sulphuric acid solution between two indium tin oxide (ITO) glass coated with the nanofiber composite. Owing to large surface area and better spacing of nanofiber network structures, PVA-GQD-Co3O4/PEDOT nanofiber composites exhibited the highest specific capacitance of 361.97 F/g compared to PEDOT (161.48 F/g), PVA/PEDOT (220.73 F/g) and PVA-GQD/PEDOT (291.86 F/g) nanofiber composites. PVA-GQD-Co3O4/PEDOT nanofiber composite also demonstrated a high specific energy and excellent specific power ranged from 16.51 to 19.98 Wh/kg and 496.10 to 2396.99 W/kg, as the current density increased from 1.0 to 5.0 A/g. In addition, the equivalent series resistance (ESR) for PVA-GQDCo3O4/ PEDOT (15.6 Ω) nanofiber composite exhibited the lowest value as compared to PEDOT (53.7 Ω), PVA/PEDOT (45.0 Ω) and PVA-GQD/PEDOT (41.9 Ω). Moreover, PVA-GQD-Co3O4/PEDOT nanofiber composite also showed an excellent stability with retention of 96% of its specific capacitance after 1000 cycles. Therefore, PVA-GQD-Co3O4/PEDOT nanofiber composite can be considered as a promising electrode material for application in supercapacitors.